Mechanical grading of structural timber and species conservation in the forest of the Congo Basin - J. Kisito Mvogo; L. M. Ayina Ohandja; L. Seba Minsili; Patrick Castera (African Journal of Environmental Economics and Management, 2020)
The aim of the present work is to propose a non-destructive experimental approach, organizing the species of the Congo Basin in four; according to the likeness of their main mechanical properties, and is also to promote the subsistence of over-consumed species in our biodiversity. The assignment of a given specie to one of the four groups takes place in return for a homogeneity test of comparison of the random variables of species to the random variable of the group. The present grading shows that, some species can be interchangeably consumed in the construction industry, without altering the 5th percentile characteristic value of mechanical properties. For a lasting management of its forest, the application of the findings of this work promotes the exploitation of less-consumed species and the conservation of exotic biodiversity of the Congo Basin.